2016
DOI: 10.1111/1365-2745.12583
|View full text |Cite
|
Sign up to set email alerts
|

Priority effects: natives, but not exotics, pay to arrive late

Abstract: Summary Assembly history can determine ecosystem structure and function by influencing the relative abundances of species. Priority effects (impacts associated with early arrival) likely promote the success of exotic invaders, which often arrive at larger propagule sizes and germinate earlier than native species and tend to grow more quickly. However, the potential for exotic species to tolerate late arrival is unknown. Using a suite of native and exotic old‐field plant species, we established a mesocosm exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
52
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 44 publications
7
52
8
Order By: Relevance
“…This is likely because late‐arriving seeded native species are outcompeted by either grasses or L. cuneata . This is in line with other experimental results demonstrating that native species are at a competitive disadvantage when arriving late (Körner et al ; Stuble & Souza ). In general, many of our seeded species, including iconic prairie species such as Liatris pycnostachya , did not establish or had low cover (e.g.…”
Section: Discussionsupporting
confidence: 93%
“…This is likely because late‐arriving seeded native species are outcompeted by either grasses or L. cuneata . This is in line with other experimental results demonstrating that native species are at a competitive disadvantage when arriving late (Körner et al ; Stuble & Souza ). In general, many of our seeded species, including iconic prairie species such as Liatris pycnostachya , did not establish or had low cover (e.g.…”
Section: Discussionsupporting
confidence: 93%
“…Changes in resources can alter competitive interactions when competitive differences between priority species and later arrivers are small. In a related study, Stuble and Souza (2016) found that the reduction in growth from arriving later was a result of both varied initial growth from priority species as well as the late arrivers' competitive ability. Similarly, Sarneel et al (2016) recently found evidence in riparian systems for increased priority effect strength in dry or variable conditions compared to wet, possibly due to species specific responses as well as abiotic effects on both the early arriving species and later community.…”
Section: Discussionmentioning
confidence: 98%
“…In grassland systems, exotic species dominance and invasion success can in part be attributed to inhibitory priority effects where exotics show large priority effects over establishing native grassland species, reducing native plant growth and diversity (Grman and Suding 2010;Martin and Wilsey 2012;Dickson et al 2012;Ulrich and Perkins 2014;Wilsey et al 2015;Stuble and Souza 2016). When native grassland species arrive first they can exclude exotic invaders (Abraham et.…”
Section: Introductionmentioning
confidence: 99%
“…Their history may thus have long‐lasting effects on species composition and abundance (Stier, Geange, Hanson, & Bolker, ; Weslien, Djupström, Schroeder, & Widenfalk, ), regulating the access to available resources (Blaustein & Margalit, ; Zuo, Li, Ma, & Callaway, ), productivity (Martin & Wilsey, ), energy flow, and nutrient cycling (Fukami et al., ). From the conservationist point of view, priority effects may even affect resistance to invasive species (De Meester et al., ; Dickson, Hopwood, & Wilsey, ; Stuble & Souza, ) and disturbance events (Symons & Arnott, ). Considering longer‐term effects, historical contingency may underlie patterns of genetic structure (Sefbom, Sassenhagen, Rengefors, & Godhe, ) and ultimately species evolution (De Meester et al., ; Fukami, Beaumont, Zhang, & Rainey, ).…”
Section: Introductionmentioning
confidence: 99%